2018
DOI: 10.29067/muvu.374610
|View full text |Cite
|
Sign up to set email alerts
|

Petrol, Dolar Kuru Ve Hi̇sse Senedi̇ Pi̇yasasi Arasindaki̇ Ortalama-Oynaklik Yayilim Etki̇si̇: Bist100 Uzeri̇ne Bi̇r Uygulama

Abstract: Petrol fiyatlarında ve dolar kurunda meydana gelen dalgalanmalar makroekonomik göstergeleri, firmaların üretim maliyetlerini ve satış gelirlerini etkiler, piyasa risk düzeyini yükseltir ve ekonomik istikrarsızlığa yol açabilir. Dolayısıyla, ekonomideki karar birimlerinin bu iki değişkendeki dalgalanmaları takip etmeleri, riski yönetebilmeleri açısından önem taşımaktadır. Dahası, finansal piyasa katılımcılarının daha iyi portföy dağılım kararları verebilmeleri için söz konusu değişkenler arasındaki oynaklık akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…When the results of the study are evaluated in terms of volatility spillover, a significant positive effect was observed from the dollar exchange rate to the ISE100 index, while no statistically significant effect was found from the oil prices to the ISE100 index. Additionally, it can be stated that negative shocks are more effective on ISE100 index volatility than positive shocks (Aktaş et al, 2018).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…When the results of the study are evaluated in terms of volatility spillover, a significant positive effect was observed from the dollar exchange rate to the ISE100 index, while no statistically significant effect was found from the oil prices to the ISE100 index. Additionally, it can be stated that negative shocks are more effective on ISE100 index volatility than positive shocks (Aktaş et al, 2018).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Using the ARCH / GARCH type variant variance models, Pala and Sönmezer (2017) has found that the policies implemented by FED during quantitative relaxation periods did not affect the oil volatility. Finally, Aktaş et al (2018) used the EGARCH model and found that shocks in oil prices had an increasing effect on the return on BIST 100.…”
Section: Literature Reviewmentioning
confidence: 99%